Carbon fiber cloth coated SixFe1-xO2 nanorod material as well as preparation method and application thereof
By using carbon fiber cloth @SixFe1-xO2 nanorod material as the negative electrode catalyst in lithium-ion batteries, the problems of structural degradation and high cost of the negative electrode material of lithium-ion batteries are solved, and high energy density, long cycle life and environmentally friendly battery performance are achieved.
Patent Information
- Application Number
- CN202411894066.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The structure of the existing lithium-ion battery anode material deteriorates during the charging and discharging process, resulting in a short cycle life, and some catalyst materials are costly and have poor environmental friendliness.
The carbon fiber fabric @SixFe1-xO2 nanorod material is used as the negative electrode catalyst of the battery and is prepared by liquid phase method and heat treatment technology to achieve nanomaterials with controllable morphology and high purity.
It improves the energy density, cycle life and charge and discharge rate of lithium-ion batteries, reduces material costs, and is environmentally friendly in processes. It is suitable for flexible batteries and optoelectronic devices and other fields.
Smart Images

Figure CN119608161A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy technology and specifically relates to a carbon fiber cloth @Si x Fe 1-x The invention discloses an O2 nanorod material and a preparation method and application thereof, and relates to a specific use of nanostructured materials. Background Art
[0002] With the rapid development of electric vehicles, energy storage systems, portable electronic devices and other fields, the market has put forward higher requirements for the energy density, cycle life, charging speed and safety of lithium-ion batteries. Although traditional graphite-based negative electrode materials are stable in commercial applications, they are difficult to meet the needs of future high-performance batteries due to their limited theoretical capacity. The research and development of new negative electrode materials for lithium-ion batteries is an important direction in the current field of battery technology. Therefore, exploring new negative electrode materials has become the key to the advancement of battery technology.
[0003] In lithium-ion batteries, negative electrode catalysts are mainly involved in the embedding (insertion) and de-embedding (extraction) processes of lithium ions. These processes occur during the charging and discharging of the battery, when lithium ions move from the positive electrode to the negative electrode (charging) or from the negative electrode back to the positive electrode (discharging). An ideal negative electrode catalyst should be able to significantly reduce the diffusion activation energy of lithium ions in the negative electrode material, thereby accelerating the reaction rate, and maintain its catalytic activity and structural stability during long-term charge and discharge cycles.
[0004] The main types of new negative electrode materials are: lithium metal, silicon-based, tin-based, transition metal oxides and carbon nanomaterials.
[0005] Lithium metal anodes have attracted much attention due to their extremely high theoretical specific capacity. In theory, lithium batteries using lithium metal anodes can significantly increase energy density, but in practical applications they face safety hazards caused by lithium dendrite growth and electrolyte decomposition. To address these issues, researchers are developing solid electrolytes and special coating technologies to inhibit the formation of lithium dendrites and improve battery safety and cycle performance.
[0006] Silicon-based materials (such as pure silicon, silicon-carbon composites, etc.) are considered to be the next generation of negative electrode materials with great potential due to their high theoretical specific capacity. Silicon undergoes a huge volume expansion during the charge and discharge process, which may cause the active material to separate from the current collector, thereby affecting the cycle stability of the battery. To solve this problem, scientists are studying nano-scale silicon particles, silicon-based alloys, and porous silicon materials to mitigate the negative effects of volume changes.
[0007] Tin-based materials also have a high theoretical specific capacity (about 994 mAh / g) and show good electrochemical performance during the charge and discharge process. However, tin-based materials also face the problem of volume expansion, so researchers are committed to developing nano-technology and methods of combining with carbon materials to improve their cycle stability and rate performance.
[0008] Transition metal oxides (such as titanium dioxide TiO2, iron oxide Fe3O4, etc.) are favored due to their low cost, environmental friendliness and stable cycle performance. The electrochemical performance of these materials can be further improved by adjusting their crystal structure or compounding with other materials.
[0009] In addition to traditional graphite, new carbon materials such as carbon nanotubes (CNTs) and graphene have also been widely studied. These materials have unique physical and chemical properties, such as high conductivity, large specific surface area, and excellent mechanical properties, which can significantly improve the electrochemical performance of batteries.
[0010] Nanostructured materials (such as nanoparticles, nanowires, nanotubes, etc.) can significantly improve the diffusion rate and electrochemical reaction activity of lithium ions due to their unique size effect and high specific surface area. The performance of the catalyst can be further optimized by regulating the morphology and size of the nanostructure.
[0011] Application in lithium-ion batteries: 1. Improve energy density: By promoting the rapid insertion and extraction of lithium ions, negative electrode catalysts help to improve the energy density of batteries, thereby extending the range of electric vehicles. 2. Extend cycle life: Catalysts can slow down the structural degradation of negative electrode materials during the charging and discharging process, extending the service life of the battery. 3. Accelerate the charging and discharging rate: Catalysts reduce the resistance to lithium ion migration, allowing the battery to complete the charging process in a shorter time, which is suitable for the needs of fast charging technology.
[0012] Although new lithium-ion battery negative electrode materials have many advantages in theory, they still face many challenges in practical applications: 1. Stability issues: The catalyst may undergo structural changes after long-term use, resulting in decreased activity. 2. Cost issues: Some highly efficient catalyst materials are expensive, limiting the possibility of their large-scale commercial application. 3. Environmental friendliness: The synthesis and processing of some catalyst materials may have adverse effects on the environment.
[0013] The research and development of negative electrode catalysts for rechargeable batteries is one of the key factors in improving battery performance. The research and development of new negative electrode materials for lithium-ion batteries will not only promote the advancement of battery technology, but also provide strong technical support for the development of clean energy, smart grids, electric vehicles and other fields.
[0014] Transition Metal Oxide Si xAs a negative electrode material for batteries, Fe1-xO2 has the advantages of high theoretical specific capacity, rich elemental resources and good chemical stability, showing broad application prospects. Although there are still some challenges in practical applications, these problems are expected to be solved through material innovation, structural design and process optimization. In the future, with the continuous deepening of research, transition metal oxides will play an increasingly important role in energy storage technologies such as lithium-ion batteries, sodium-ion batteries and potassium-ion batteries, and provide new solutions for achieving high-performance, low-cost and environmentally friendly battery technologies. Therefore, a simple method and low cost are used to prepare nano-Si with controllable morphology and high purity. x Fe 1-x O2 is of great significance. Summary of the invention
[0015] In order to solve at least one of the above problems, the present invention provides a carbon fiber cloth @Si x Fe 1-x O2 nanorod material and its preparation method and application.
[0016] In order to achieve the above object, the present invention adopts the following technical means: The first invention of the present invention provides a carbon fiber cloth @Si x Fe 1-x The preparation method of O2 nanorod material comprises the following steps: S1. Dissolve the silicon source and the iron source in a mixed solution of ethanol and ethylene glycol, and stir well to form a solution A; S2, dissolving hexamethylenetetramine in solution A, stirring thoroughly to form solution B; S3, dissolving urea in solution B, stirring thoroughly to form solution C; S4, put the solution C and the carbon fiber cloth into a high-pressure reactor, put it into a constant temperature drying oven, react at a certain temperature for a period of time, cool the high-pressure reactor naturally to room temperature, wash it with ethanol and deionized water for multiple times, and dry it to obtain the carbon fiber cloth @Si x Fe 1-x (OH)4 nanorod materials; S5, carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod materials.
[0017] In some embodiments of the present invention, in steps S1, S2, and S3, the molar ratio of the silicon source, the iron source, hexamethylenetetramine, and urea is 1:(3-5):(0.1-4):(5-700).
[0018] In some embodiments of the present invention, x ranges from 0.16 to 0.25.
[0019] In some embodiments of the present invention, in step S1, the silicon source is silicon tetrachloride or ethyl silicate, and the iron source is ferric nitrate, ferric acetate, ferric chloride or a mixture of the two or more in equal proportions.
[0020] In some embodiments of the present invention, in step S1, the volume ratio of ethanol to ethylene glycol in the mixed solution is (15-20):1.
[0021] In some embodiments of the present invention, in step S1, the concentration of solution A is 0.02-0.2 mol / L.
[0022] In some embodiments of the present invention, the stirring time in steps S1, S2 and S3 is 10-60 min.
[0023] In some embodiments of the present invention, the reaction temperature in step S4 in the drying oven is 100-200° C. and the reaction time is 5-24 h.
[0024] In some embodiments of the present invention, the annealing temperature in step S5 is 200-800° C. and the annealing time is 5-200 min.
[0025] The second aspect of the present invention provides a carbon fiber cloth @Si prepared by the preparation method described in the first aspect x Fe 1-x O2 nanorod material, the carbon fiber cloth @Si x Fe 1-x The length of O2 nanorod materials is 10-100 nm.
[0026] The third aspect of the present invention provides the carbon fiber cloth @Si described in the second aspect. x Fe 1-x Application of O2 nanorod materials as battery negative electrode catalysts.
[0027] The present invention also provides the carbon fiber cloth@Si x Fe 1-x Application of O2 nanorod materials in the preparation of lithium-ion rechargeable batteries.
[0028] Beneficial Effects of the Invention Compared with the prior art, the present invention has the following beneficial effects: the present invention combines the liquid phase method with the heat treatment technology to successfully synthesize the carbon fiber cloth @Si x Fe1-xO2 nanorod material. Carbon fiber cloth@Si x Fe 1-xThe preparation method of O2 nanorod material does not require expensive instruments and equipment, and through reasonable process control, carbon fiber cloth@Si x Fe 1-x Preparation of O2 nanorod material. The raw materials used in the present invention are cheap and easy to obtain, the synthesis process is simple, the cost is low, the reaction cycle is short, and there is no pollution to the environment. The prepared carbon fiber cloth @Si x Fe 1-x The O2 nanorod material is uniform in size, adjustable in size, and well dispersed. The resulting product is uniform and has a novel morphology. As a flexible negative electrode material, it has high charge and discharge capacity and long cycle life, and is widely used in flexible batteries, optoelectronic devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The carbon fiber cloth @Si prepared in Example 1 x Fe 1-x Scanning electron microscope photos of O2 nanorod materials at a resolution of 10.0 μm (A) and 1.00 μm (B); Figure 2 The carbon fiber cloth @Si prepared in Example 4 x Fe 1-x Scanning electron microscope photos of O2 nanorod materials at a resolution of 10.0 μm (A) and 1.00 μm (B); Figure 3 The carbon fiber cloth @Si prepared in Example 7 x Fe 1-x Scanning electron microscope photos of O2 nanorod materials at a resolution of 10.0 μm (A) and 1.00 μm (B); Figure 4 The carbon fiber cloth@Si prepared in Example 10 x Fe 1-x Scanning electron microscope photograph of O2 nanorod material at a resolution of 30.0μm (A) and at a resolution of 1.00μm (B). DETAILED DESCRIPTION
[0030] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.
[0032] A carbon fiber cloth @Si x Fe 1-x The preparation method of O2 nanorod material comprises the following steps: S1. Dissolve the silicon source and the iron source in a mixed solution of ethanol and ethylene glycol in a volume ratio of (15-20):1, and stir for 10-60 min to fully stir and evenly form solution A; S2. Dissolve hexamethylenetetramine in solution A and stir for 10-60 min to fully stir and evenly form solution B; S3, dissolving urea in solution B, stirring for 10-60 min to fully stir and evenly form solution C; S4, put solution C and carbon fiber cloth into a high-pressure reactor, put it into a constant temperature drying oven, react at a reaction temperature of 100-200 ° C for 5-24 h, cool the high-pressure reactor naturally to room temperature, wash it with ethanol and deionized water for multiple times, and dry it to obtain carbon fiber cloth @Si x Fe 1-x (OH)4 nanorod materials; S5, carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material is placed in a muffle furnace and annealed in an air environment at a temperature of 200-800°C and an annealing time of 5-200 min to obtain a carbon fiber cloth@SixFe1-xO2 nanorod material.
[0033] Among them, in steps S1, S2, and S3, the molar ratio of the silicon source, the iron source, hexamethylenetetramine, and urea is 1:(3-5):(0.1-4):(5-700), wherein the value range of x is 0.16-0.25.
[0034] In step S1, the silicon source is silicon tetrachloride or ethyl silicate, and the iron source is ferric nitrate, ferric acetate, ferric chloride or a mixture thereof. When the iron source is a mixture, it is a mixture of several substances in equal proportions.
[0035] In step S1, the concentration of solution A is 0.02-0.2 mol / L.
[0036] The present invention also provides the above-mentioned preparation method to prepare carbon fiber cloth @Six Fe 1-x O2 nanorod materials, carbon fiber cloth@Si x Fe 1-x The length of O2 nanorod materials is 10-100 nm.
[0037] The present invention also provides the carbon fiber cloth @Si x Fe 1-x Application of O2 nanorod materials as battery negative electrode catalysts.
[0038] The present invention also provides the carbon fiber cloth @Si x Fe 1-x Application of O2 nanorod materials in the preparation of lithium-ion rechargeable batteries.
[0039] The above technical solution of the present application is further described in detail below in conjunction with specific implementation methods.
[0040] Example 1 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0041] Prepared carbon fiber cloth @Si x Fe 1-x Scanning electron microscopy of O2 nanorods Figure 1As shown, the left and right figures are respectively carbon fiber cloth @Si x Fe 1-x SEM images of O2 nanorod materials at resolutions of 10.0 μm and 1.00 μm. From the SEM images, we can see that the prepared carbon fiber cloth@Si x Fe 1-x The O2 nanorod material has relatively uniform size and good crystallinity.
[0042] Example 2 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: The details are as follows: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric nitrate in 200 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0043] Example 3 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of a mixed iron source in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, stirring for 60 minutes to form a solution A; the mixed iron source is ferric nitrate, ferric acetate, and ferric chloride mixed in equal proportions to obtain a mixture; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 60 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 60 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0044] Example 4 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of ethyl silicate and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.01 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 180°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0045] Prepared carbon fiber cloth @Si x Fe 1-x Scanning electron microscopy of O2 nanorods Figure 2 As shown, the left and right figures are respectively carbon fiber cloth @Six Fe 1-x SEM images of O2 nanorod materials at resolutions of 10.0 μm and 1.00 μm. From the SEM images, we can see that the prepared carbon fiber cloth@Si x Fe 1-x The O2 nanorod material has relatively uniform size and good crystallinity.
[0046] Example 5 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of a mixed iron source in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, stirring for 30 minutes to form a solution A; the mixed iron source is a mixture of ferric nitrate and ferric acetate in equal proportions; Step 2, dissolving 4 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 8 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0047] Example 6 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric acetate in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 400℃ for 60min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0048] Example 7 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of a mixed iron source in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, stirring for 30 minutes to form a solution A; the mixed iron source is a mixed iron source of ferric acetate and ferric chloride; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 120 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0049] Prepared carbon fiber cloth @Si x Fe 1-x Scanning electron microscopy of O2 nanorods Figure 3 As shown, the left and right figures are respectively carbon fiber cloth @Si x Fe 1-xSEM images of O2 nanorod materials at resolutions of 10.0 μm and 1.00 μm. From the SEM images, we can see that the prepared carbon fiber cloth@Si x Fe 1-x The O2 nanorod material has relatively uniform size and good crystallinity.
[0050] Example 8 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric nitrate in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 1 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 750℃ for 60min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0051] Example 9 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 0.5 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0052] Example 10 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.02 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 24 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 550℃ for 60min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0053] Prepared carbon fiber cloth @Si x Fe 1-x Scanning electron microscopy of O2 nanorods Figure 4 As shown, the left and right figures are respectively carbon fiber cloth @Si x Fe 1-xSEM images of O2 nanorod materials at resolutions of 30.0 μm and 1.00 μm. From the SEM images, we can see that the prepared carbon fiber cloth@Si x Fe 1-x The O2 nanorod material has relatively uniform size and good crystallinity.
[0054] Comparative Example 1 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2: dissolve 0.05 mol of urea in solution A and stir for 30 min to form solution B; Step 3: Place solution B and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 4: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0055] Comparative Example 2 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric chloride in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3: Place solution B and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 4: The obtained carbon fiber cloth @Six Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0056] Comparative Example 3 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 18 mmol of ferric nitrate in 100 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 0.05 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.08.
[0057] Comparative Example 4 A carbon fiber cloth @Si x Fe 1-x O2 nanorod material, the preparation method thereof comprises the following steps: Step 1, dissolving 1.5 mmol of silicon tetrachloride and 6 mmol of ferric nitrate in 500 ml of a mixed solution of ethanol and ethylene glycol in a volume ratio of 19:1, and stirring for 30 minutes to form a solution A; Step 2, dissolving 1 mmol of hexamethylenetetramine in solution A and stirring for 30 min to form solution B; Step 3, dissolving 3 mol of urea in solution B and stirring for 30 min to form solution C; Step 4: Place solution C and carbon fiber cloth into a high-pressure reactor, react at 160°C in a constant temperature drying oven for 12 hours, cool naturally to room temperature, wash with ethanol and deionized water for multiple times, and dry to obtain carbon fiber cloth@Si x Fe 1-x (OH)4 nanorod materials; Step 5: The obtained carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed at 350°C for 60 min in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x is 0.2.
[0058] In the above embodiments and comparative examples, the sum of the silicon source and the iron source is equal to 1, and the value of x can be calculated based on the usage ratio of the silicon source and the iron source.
[0059] Embodiment 11 The performance of the negative electrode material of lithium batteries directly affects the cycle life, charge and discharge efficiency and safety of the battery. The performance test results of the flexible negative electrode prepared by the carbon fiber cloth@SixFe1-xO2 nanorod material prepared in Examples 1-10 and Comparative Examples 1-4 and applied in the battery are shown in Table 1.
[0060] The battery was charged and discharged using a battery circulation system, and the battery circulation system used was the CT2001A model produced by Wuhan Blue Electric Electronics Co., Ltd.
[0061] Table 1 Performance test results
[0062] The results show that the flexible negative electrode made of carbon fiber cloth@SixFe1-xO2 nanorods prepared by the method of the present invention is used in the battery, and its specific capacity is significantly higher than that of the control example. After 1500 cycles, the specific capacity retention rate is also significantly higher than that of the control example, showing good ability to store electricity and charge and discharge cycle performance.
[0063] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.
Claims
1. A carbon fiber cloth @Si x Fe 1-x The method for preparing O2 nanorod material is characterized in that: The following steps are involved: S1. Dissolve the silicon source and the iron source in a mixed solution of ethanol and ethylene glycol, and stir well to form a solution A; S2, dissolving hexamethylenetetramine in solution A, stirring thoroughly to form solution B; S3, dissolving urea in solution B, stirring thoroughly to form solution C; in steps S1, S2, and S3, the molar ratio of silicon source, iron source, hexamethylenetetramine, and urea is 1:(3-5):(0.1-4):(5-700); S4. Put solution C and carbon fiber cloth into a high-pressure reactor, put it into a constant temperature drying oven, react for a period of time at a certain temperature, cool the high-pressure reactor naturally to room temperature, wash it with ethanol and deionized water for multiple times, and dry it to obtain carbon fiber cloth @Si x Fe 1-x (OH)4 nanorod materials; S5, carbon fiber cloth @Si x Fe 1-x The (OH)4 nanorod material was placed in a muffle furnace and annealed in air to obtain carbon fiber cloth@Si x Fe 1-x O2 nanorod material, wherein the value of x ranges from 0.16 to 0.
25.
2. The preparation method according to claim 1, characterized in that: In step S1, the silicon source is silicon tetrachloride or ethyl silicate, and the iron source is ferric nitrate, ferric acetate, ferric chloride or a mixture of the two or more thereof in equal proportions.
3. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of ethanol to ethylene glycol in the mixed solution is (15-20):
1.
4. The preparation method according to claim 1, characterized in that: In step S1, the concentration of solution A is 0.02-0.2 mol / L.
5. The preparation method according to claim 1, characterized in that: The stirring time in steps S1, S2 and S3 is 10-60 min.
6. The preparation method according to claim 1, characterized in that: The reaction temperature of step S4 in the drying oven is 100-200° C. and the reaction time is 5-24 h.
7. The preparation method according to claim 1, characterized in that: In the step S5, the annealing temperature is 200-800° C. and the annealing time is 5-200 min.
8. Carbon fiber cloth@Si is prepared by the preparation method according to any one of claims 1 to 7 x Fe 1-x O2 nanorod material, characterized by: The carbon fiber cloth@Si x Fe 1-x The length of O2 nanorod materials is 10-100 nm.
9. The carbon fiber cloth@Si according to claim 8 x Fe 1-x Application of O2 nanorod materials as battery negative electrode catalysts.
10. The carbon fiber cloth@Si according to claim 8 x Fe 1-x Application of O2 nanorod materials in the preparation of lithium-ion rechargeable batteries.
Citation Information
Cited By
Self-supporting flexible silver-rich electrode and preparation method and application thereof
CN120341293A
A self-supporting flexible silver-rich electrode and its preparation method and application
CN120341293B